2008
DOI: 10.1021/es702451p
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentrations of Polybrominated Diphenyl Ethers (PBDEs) and Polybrominated Biphenyl (PBB) in the United States Population: 2003–2004

Abstract: Polybrominated diphenyl ethers (PBDEs) and 2,2',4,4',5,5'-hexabromobiphenyl (BB-153) are chemicals known as brominated flame retardants. We have assessed the exposure status of the United States population to PBDEs and BB-153 and explored associations with demographic information, including participants' age, sex, and race/ethnicity. A total of 2,062 serum samples, from participants in the National Health and Nutrition Examination Survey (NHANES) 2003-2004 aged 12 years and older, were analyzed for PBDEs and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
297
17
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 324 publications
(348 citation statements)
references
References 18 publications
33
297
17
1
Order By: Relevance
“…The relationships between the PBDE concentration and age in the nonoccupationally exposed residents from e-waste recycling area were investigated. Sjödin et al (2008) observed a curvilinear trend between log-transformed lipid BDE concentrations in serum and age in the participants from America. In the present study, we observed a similar trend with the lowest PBDE concentrations in the adult groups (19e60 years age group) (Fig.…”
Section: Pbde Levels and Profiles In Hairmentioning
confidence: 80%
See 2 more Smart Citations
“…The relationships between the PBDE concentration and age in the nonoccupationally exposed residents from e-waste recycling area were investigated. Sjödin et al (2008) observed a curvilinear trend between log-transformed lipid BDE concentrations in serum and age in the participants from America. In the present study, we observed a similar trend with the lowest PBDE concentrations in the adult groups (19e60 years age group) (Fig.…”
Section: Pbde Levels and Profiles In Hairmentioning
confidence: 80%
“…It is worth to compare the PBDE profiles in the hair with the serum samples reported by other previous studies (Antignac et al, 2009;Bi et al, 2007;Harrad and Porter, 2007;Kalantzi et al, 2010;Sjödin et al, 2008;Zhu et al, 2009). Due to the sets of congeners reported in different studies are not identical each other, we could only summed the most commonly reported congeners (BDE 47,99,100,153,154 and 183) and normalized them to 100%.…”
Section: Roles Of Dust As Source Of Hair Bfrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies with a prospective design and more representative controls would help reveal the true effect of PBDEs on breast cancer. In addition, PBDE levels were found inversely related to age, so the body burden of PBDEs measured at or near the time of diagnosis cannot reveal the real damage for breast cancer [57].…”
Section: Polybrominated Diphenyl Ethers (Pbdes)mentioning
confidence: 99%
“…Analysis of data from National Health and Nutrition Examination Survey (NHANES) [2003][2004] indicated that PBB-153 was detected in 83% of samples (Sjödin et al, 2008). Nonetheless, analysis of archived serum pools indicated that PBB-153 concentrations had been decreasing in the USA, the only country Landrigan et al (1979).…”
Section: Exposure Of the General Populationmentioning
confidence: 99%